Rancang Bangun Pita Lengan Metronome dengan Koneksi Bluetooth berbasis Mikrokontroler dan Android - Jezriel Lukas Lumbantobing; Dahnial Syauqy; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
To determine the tempo in a song, Metronome is needed to help as a tool, because the metronome will produce sound on every beat of the song. However, the metronome used on the market is less effective in terms of helping the tempo during live shows and can also interfere with hearing when using earphones if the volume of the metronome should be increased. A metronome arm band can be a solution because it produces a vibration that can be felt in the hands. Users can also set the desired number of beats per minute (BPM) via a smartphone application that is connected via bluetooth. There are 3 elements to be used, which are; Smartphone as input, ESP32 as processor and Vibration Motor as an output. Because metronomes must have high accuracy in keeping the tempo, RTOS is needed to help avoid interruptions when the user sends other commands during vibration. There are 3 tests carried out to determine the accuracy of the Metronome Bracelet. The first test to see whether 60 bpm on the metronome produces an output of exactly 60 beats per minute. The second and third tests are also the same but at different tempo numbers, which are 90 and 120. The expected output of the metronome should be exactly like the number shown in the bpm value on the Metronome Bracelet, where 60 produces a vibration accuracy of 60 bpm, 90 produces 90 bpm, and 120 produces 120 bpm.